Effectiveness of Initial Transarterial Chemoembolization for Hepatocellular Carcinoma Among Medicare Beneficiaries - Sanoff, Hanna K. (J Natl Compr Canc Netw, 2015)
BACKGROUND: Optimal administration of transarterial chemoembolization (TACE), the standard approach for intermediate stage hepatocellular carcinoma (HCC), requires clinical and technical expertise. We sought to evaluate if TACE retains its effectiveness when administered across a broad range of healthcare settings. With increasing use of yttrium(90) radioembolization (Y(90)), we explored the effectiveness of Y(90) compared with TACE. METHODS: HCC patients diagnosed from 2004–2009 treated initially with TACE or Y(90) were identified from the Surveillance Epidemiology and End-Results (SEER)-Medicare linkage. Key covariates included prediagnosis AFP screening, complications of cirrhosis, and tumor extent. Effect of treatment, patient, and healthcare system factors on overall survival (OS) was evaluated using multivariable Cox proportional hazards. Stratified OS estimates are provided. Propensity score (PS) weighting was used to compare effectiveness of Y(90) to TACE. RESULTS: Of 1,528 with intra-arterial embolization, 577 had documentation of concurrent chemotherapy (e.g. TACE). Median OS was 21 months (95% CI 18–23) following TACE, 9 months (95% CI 1–41) following Y(90). Refined survival estimates stratified by stage, AFP screening, and liver comorbidity are presented. Ninety day mortality after TACE was 21–25% in patients with extrahepatic spread or vascular invasion. In the PS-weighted analysis, Y(90) was associated with inferior survival, aHR 1.39 (95% CI 1.02–1.90). CONCLUSIONS: The effectiveness of TACE is generalizable to Medicare patients receiving care in a variety of treatment settings. However, early post-treatment mortality is high in patients with advanced disease. We found no evidence for improved outcomes with Y(90) compared with TACE. Survival estimates from this large cohort can be used to provide prognostic information to patients considering palliative TACE.